Sustainable Development and Innovation in the Energy Sector - Steger, Ulrich; Achterberg, Wouter; Blok, Kornelis; Bode, Henning; Frenz, Walter; Gather, Corinna; Hanekamp, Gerd; Imboden, Dieter; Jahnke, Matthias; Kost, Michael; Kurz, Rudi; Nutzinger, Hans Gottfried; et al. (Springer Berlin Heidelberg : Imprint: Springer, 2005)
Almost every energy scenario assumes an enormous growth in the demand for energy in the coming decades. Meanwhile, at international conferences and other venues, the primary concern is massive reduction of greenhouse gas emissions, especially of the CO2 produced by fossil-fuel energy consumption. Experts also point out the political risk of depending on petroleum and remind us of the fact that resources are not inexhaustible. This timely book explores: how these conflicting scenarios could be reconciled; how can we shape a more sustainable energy system from the existing one; and possible technological progress and innovations to enable a brighter future. It also addresses the reality that there exists no consensus on the extent to which innovations can really contribute to reconciling ever-growing energy consumption, availability of resources and the environment, and the structural demands on any energy system.